Impact of climate change on sustainable crop production and consumption (SDG-12): empirical evidence from rural Bangladesh - Shamshad Ferdousee; Md. Mahbubur Rahman; Ashraful Islam; S.M. Arif Mahmud (Technology in Agronomy)
The present study sheds light on recent climate change and its connection with sustainable production and consumption in the northern region of Bangladesh. The study adopted various qualitative research tools to explore research questions and study-specific objectives. It utilized non-probability purposive sampling technique to choose the study locations and 20 informants from the selected study areas. The research applied Key Informant Interviews (KIIs) and Focus Group Discussions (FGDs), as qualitative tools to obtain the necessary information from the selected informants. Utilizing the thematic analysis technique as part of the qualitative method, the study categorized the collected data into a range of sub-themes central to the significant findings of this study. The study found that various climatic events, such as less rainfall, drought, and heat waves, decreased agricultural land fertility, seriously affecting crop production, and diversification. Additionally, recent climate change led to market oscillation, enhanced financial risks, and price hikes in some daily necessary foodstuffs. These climatic events further contributed to reducing food availability and stability of crop production in the study area, worsening the current food security among the study group. It is recommended that the Government of Bangladesh (GoB) should take evidence-based measurements, for instance, climate-resilient agricultural loans, better seeds, and regular irrigation, which are required to promote climate-resilient crop production and to ensure better nutritional food production among the country's people.